2023
DOI: 10.3390/ijerph20010810
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Zero Tillage with Residue Management in Rice–Wheat System in the Indo-Gangetic Plains: Impact on Thermal Sensitivity of Soil Organic Carbon Respiration and Enzyme Activity

Abstract: The impact of global warming on soil carbon (C) mineralization from bulk and aggregated soil in conservation agriculture (CA) is noteworthy to predict the future of C cycle. Therefore, sensitivity of soil C mineralization to temperature was studied from 18 years of a CA experiment under rice–wheat cropping system in the Indo-Gangetic Plains (IGP). The experiment comprised of three tillage systems: zero tillage (ZT), conventional tillage (CT), and strip tillage (ST), each with three levels of residue management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 86 publications
2
3
0
Order By: Relevance
“…Our factorial analysis revealed that enhanced tillage practices significantly contributed to an increase in soil CO 2 release by 6.1%, a finding consistent with other studies conducted in the U.S. (Bai et al., 2019; Dutta et al., 2023). This effect can likely be attributed to the fact that tillage disrupts the soil, accelerating the rate of decomposition of soil organic matter (Bai et al., 2019; Mishra et al., 2010; Olson et al., 2014; Salinas‐Garcia et al., 1997) and diminishing the biomass of fungi and earthworms (Briones & Schmidt, 2017; Lavelle et al., 1999).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our factorial analysis revealed that enhanced tillage practices significantly contributed to an increase in soil CO 2 release by 6.1%, a finding consistent with other studies conducted in the U.S. (Bai et al., 2019; Dutta et al., 2023). This effect can likely be attributed to the fact that tillage disrupts the soil, accelerating the rate of decomposition of soil organic matter (Bai et al., 2019; Mishra et al., 2010; Olson et al., 2014; Salinas‐Garcia et al., 1997) and diminishing the biomass of fungi and earthworms (Briones & Schmidt, 2017; Lavelle et al., 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Numerous field investigations and meta‐analyses have provided evidence that intensified agricultural management practices significantly exacerbate soil GHG emissions in croplands (Bai et al., 2019; Bo et al., 2022; Cui et al., 2013; Davidson, 2009; Dutta et al., 2023; Gupta et al., 2021; Lu et al., 2021; Reay et al., 2012). However, these practices also hold the potential to confer advantages for SOC change in croplands due to their substantial mitigation benefits, cost‐effectiveness, and additional positive outcomes such as improved soil and water quality and preservation of biodiversity (Fargione et al., 2018; Li et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our factorial analysis revealed that enhanced tillage practices significantly contributed to an increase in soil CO 2 release by 6.1%, a finding consistent with other studies conducted in the U.S. (Bai et al, 2019;Dutta et al, 2023). This effect can likely be attributed to the fact that tillage disrupts the soil, accelerating the rate of decomposition of soil organic matter (Mishra et Furthermore, the disturbance caused by tillage introduces more oxygen into the soil, temporarily altering the anaerobic environment.…”
Section: Impacts Of Agricultural Management Practices On Net Ghg Balancesupporting
confidence: 89%
“…Numerous field investigations and meta-analyses have provided evidence that intensified agricultural management practices significantly exacerbate soil GHG emissions in croplands (Cui et al, 2013;Reay et al, 2012;Lu et al, 2021;Davidson et al, 2009;Bai et al, 2019;Dutta et al, 2023;Bo et al, 2022;Gupta et al, 2021). However, these practices also hold the potential to confer advantages for SOC sequestration in croplands due to their substantial mitigation benefits, cost-effectiveness, and additional positive outcomes such as improved soil and water quality and preservation of biodiversity (Fargione et al, 2018;.…”
Section: Impacts Of Agricultural Management Practices On Net Ghg Balancementioning
confidence: 99%
“…Presently, limited information is available in the literature on the role of crop residue heterogeneity on the dynamics of different enzymatic activities in soil. However, studies have investigated the effects of organic residue amendments on soil enzymatic activities, but most of these studies have focused on specific residue types or narrowly defined chemical compositions [37,38]. To fully comprehend the influence of organic residues on soil enzymatic activities, it is crucial to consider the diverse range of residues commonly available in agricultural systems.…”
Section: Introductionmentioning
confidence: 99%